Heterobimetallic Zn2+/Co2+ Monocarboxylates as Precursors for ZnO Microparticles Doped with Cobalt and its Photocatalytic Activity in Methyl Orange Oxidation - Correa, Hélder Inocêncio Ferreira; Ramalho Jr, Ralf Ricardo; Oliveira, Adhimar Flávio; Lisboa, Fabio da Silva (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
In this work, zinc oxide microparticles doped with cobalt were prepared from two novel layered heterobimetallic monocarboxylates as precursors to obtain uniform shape and size oxide particles, aiming for a photocatalytic removal of methyl orange. Both monocarboxylates produced ZnO doped with Co2O3 after calcination at 700 or 900 °C, in 7 or 12 hours. The particles formed by the laurate precursor presented rectangular prisms shaped, while those formed from stearate were sphere-like particles. All particles ranged from 0.1 to 0.9 μm size, with a direct bandgap of 2.2 to 2.6 eV and an indirect bandgap of 0.25 to 1.70 eV. The ZnO/Co prepared presented photocatalytic activity on methyl orange photodegradation. The solid prepared by the laurate precursor showed a photodegradation rate of 0.00185 min-1, while the one obtained from the stearate precursor presented a photodegradation rate of 0.00860 min-1, eight times greater. These results show that the material may be very useful in removing dyes from water samples. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).